Assessing the Targeting of Social Assistance Benefits - Karpuškienė, Vita (Ekonomika, 1999)
The main purposes of this article are to introduce the notion of benefit’s targeting and evaluate it for Lithuanian social assistance benefit scheme. Targeting has two aspects. First is concerned with avoiding leakage, i. e. benefits should go only to those who need them. Second aspect of targeting is concerned with avoiding gaps, i. e. benefit should go to all of poor. Failure can arise either because eligibility rules prevent some needy groups from applying, or because take-up is less than 100 per cent. In the latter case, on the demand side, eligible claimants may not apply, either for lack of information or because of complicated bureaucratic procedure or stigma. On the supply side an eligible person may apply, but be refused, either in error or because of discrimination.